MULTIFUNCTIONAL MICROBIAL COMPLEX FOR THE AGRICULTURAL INTEGRAL SYSTEMS - В. В. Чайковська; Я. В. Чабанюк; О. В. Шерстобоева (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2007)
It has been established the positive effect of introduction of the multifunctional complex of microorganisms of rhizosphere winter 'wheat. High activity of different strains can increase general biological activity, activate destruction of cellulose the amounts in the soils, establishing antifungal capacity of the soil.